2018
DOI: 10.3233/jad-171121
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Diet, Its Components, and Amyloid Imaging Biomarkers

Abstract: Findings are consistent with previous studies suggesting that higher adherence to a MeDi pattern and higher vegetable consumption are associated with better neuroimaging biomarker profile. Prospective studies are needed to validate current findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 50 publications
1
31
0
Order By: Relevance
“…However, Luciano et al found no associations of meat intake with cortical thickness and volume in the Scottish Lothian birth cohort with following up for 7 years [61]. In addition, the Mayo clinic study of aging (MCSA) observed no associations between meat consumption and Aβ abnormality among 278 older participants [62]. Therefore, whether meat intake is in relation to changes of brain volume or Aβ deposit remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, Luciano et al found no associations of meat intake with cortical thickness and volume in the Scottish Lothian birth cohort with following up for 7 years [61]. In addition, the Mayo clinic study of aging (MCSA) observed no associations between meat consumption and Aβ abnormality among 278 older participants [62]. Therefore, whether meat intake is in relation to changes of brain volume or Aβ deposit remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Two cross-sectional studies in the American population found an association between higher adherence to a MeDi pattern and lower 11C-PiB PET scan measurements of A β deposition as well as higher glucose metabolism as observed by FDG-PET scans [61, 62]. Higher MeDi adherence was also associated with reduced cerebral A β accumulation over time (up to 3 years) in a longitudinal study performed by Rainey-Smith et al on older Australian adults classified as “A β accumulators” and thus considered to be on the way to AD [63].…”
Section: Mediterranean Diet (Medi) and Ad Preventionmentioning
confidence: 99%
“…Whereas unhealthy diets, constituting refined grains, sweetened desserts, high fat dairy products, and processed/red meat, have been associated with a higher risk of AD ( Olsson et al, 2015 ; Samadi et al, 2020 ). The main healthy dietary patterns identified in respect to risk of AD, include the MD ( Scarmeas et al, 2006a ; Scarmeas et al, 2006b ; Scarmeas et al, 2009b ; Gu et al, 2010a ; Gu et al, 2010b ; Gardener et al, 2012 ; Morris et al, 2015 ; Olsson et al, 2015 ; Hill et al, 2018 ; Vassilaki et al, 2018 ), dietary approaches to stop hypertension (DASH) diet ( Morris et al, 2015 ), Mediterranean-DASH intervention for neurodegenerative delay (MIND) diet ( Morris et al, 2015 ), healthy eating index (HEI) diet ( Eskelinen et al, 2011 ; Olsson et al, 2015 ), seafood-rich diet ( Morris et al, 2003b ; Devore et al, 2009 ; Morris et al, 2016 ), soy-based diet ( Ozawa et al, 2013 ), and low-fat diet and high-protein diet ( Olsson et al, 2015 ; Fernando et al, 2018 ; Hill et al, 2018 ).…”
Section: Disscusionmentioning
confidence: 99%
“…A healthy diet is recognized to have beneficial anti-inflammatory, antioxidant, and metabolic effects, which may in turn induce anti-neurodegenerative benefits ( Seeram, 2006 ; Berti et al, 2015 ). Therefore, healthy diets (including DASH, MD, MIND, seafood-rich, HEI, soy-based, capsaicin-rich, and low-fat and high-protein diets) may reduce oxidative stress, chronic inflammation and accumulation of amyloid-β ( Morris et al, 2003a ; Morris et al, 2003b ; Scarmeas et al, 2006a ; Scarmeas et al, 2006b ; Devore et al, 2009 ; Scarmeas et al, 2009b ; Gu et al, 2010a ; Gardener et al, 2012 ; Ozawa et al, 2013 ; Olsson et al, 2015 ; Morris et al, 2015 ; Morris et al, 2016 ; Fernando et al, 2018; Hill et al, 2018 ; Vassilaki et al, 2018 ). Moreover, few studies have focused on the ability of unhealthy diets, particularly diets high in fat and sugar-sweetened beverages, to promote oxidative stress, inflammation, and the developing of amyloid-β and, consequentially, AD ( Morris et al, 2003b ; Laitinen et al, 2006 ; Luchsinger et al, 2007 ; Gu et al, 2011 ; Ylilauri et al, 2017 ; Hill et al, 2018 ).…”
Section: Disscusionmentioning
confidence: 99%
See 1 more Smart Citation